BK POLYOMAVIRUS (BKPyV) INFECTION IN RENAL TRANSPLANTATION: VIRAL CHARACTERISTICS, DIVERSITY, REACTIVATION, RISK FACTORS AND LABORATORY DIAGNOSIS - Miljanovic, Danijela; Lazarevic, Ivana; Banko, Ana; Knezevic, Aleksandra; Stanojevic, Maja; Jankovic, Marko; Cirkovic, Andja; Cupic, Maja (Medical Research, 2026)
BK polyomavirus (BKPyV) is a ubiquitous human polyomavirus, and more than 80% of the human population is seropositive for BKPyV. Following primary infection, which is usually asymptomatic, BKPyV establishes lifelong persistence in renal epithelial cells. In recent years, the use of potent immunosuppressive drugs after transplantation has led to an increasing incidence of BKPyV reactivation in patients with organ transplants, placing BKPyV among the major risk factors for graft loss in kidney transplant recipients. This review provides an overview of BKPyV infection in the context of renal transplantation from a virologist's perspective. The first part of the review covers basic virology, including virion structure, genome organisation, life cycle, mechanisms of lifelong BKPyV persistence, and basic epidemiology. The meeting points of basic and clinical virology are explained through BKPyV diversity and its clinical implications. The clinical aspects are discussed, including donor- and recipient-related risk factors for BKPyV reactivation, the clinical importance of BKPyV subtyping, and serotype-specific immunity. In the second part of the review, emphasis is placed on the possibilities of laboratory diagnostics of BKPyV infection. Finally, the review provides current international recommendations for screening and monitoring of BKPyV infection in the post-transplant period. By combining virological, clinical, and diagnostic aspects, this review highlights the complexity of BKPyV infection after kidney transplantation, underscoring the need for optimised monitoring strategies, further research into the clinical importance of viral diversity, and improvements in therapeutic protocols to control BKPyV infection after kidney transplantation.
Keywords: BK polyomavirus, BKPyV, polyomavirus-associated nephropathy, risk factors, kidney transplantation